2016
DOI: 10.1007/s00775-016-1336-0
|View full text |Cite
|
Sign up to set email alerts
|

Ferritins: furnishing proteins with iron

Abstract: Ferritins are a superfamily of iron oxidation, storage and mineralization proteins found throughout the animal, plant, and microbial kingdoms. The majority of ferritins consist of 24 subunits that individually fold into 4-α-helix bundles and assemble in a highly symmetric manner to form an approximately spherical protein coat around a central cavity into which an iron-containing mineral can be formed. Channels through the coat at inter-subunit contact points facilitate passage of iron ions to and from the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 99 publications
5
123
1
1
Order By: Relevance
“…8,12,40,44 In contrast to our findings with P. aeruginosa , FtnA is the main iron accumulator in E. coli , while the function of Bfr remains unknown. 35 The distinct physiological roles played by P. aeruginosa BfrB and E. coli Bfr are fascinating in the context that structural and biochemical characterization of these proteins have revealed important differences, despite very similar quaternary structures.…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…8,12,40,44 In contrast to our findings with P. aeruginosa , FtnA is the main iron accumulator in E. coli , while the function of Bfr remains unknown. 35 The distinct physiological roles played by P. aeruginosa BfrB and E. coli Bfr are fascinating in the context that structural and biochemical characterization of these proteins have revealed important differences, despite very similar quaternary structures.…”
Section: Resultscontrasting
confidence: 85%
“…Although the reasons why bacteria would require two types of 24-mer iron storage proteins remain enigmatic, attempts to address the issue have led to the suggestion that the specific physiological roles played by Ftns and Bfrs are distinct in different bacteria. 40 For example, whereas FtnA is the main iron accumulator in E. coli cells, 35 the same role has been attributed to Bfr in Salmonella enterica typhimurium. 41 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand it is believed that in E.coli ferritin A (EcFtnA) three Fe(II) are simultaneously oxidized in sites A, B, and C. 21 On the basis of these data the diversity view has emerged claiming that the mechanism of Fe(II) oxidation and Fe(III) storage varies among ferritins. 14,15,22 In contrast our studies of the hyperthermophilic archaeal ferritin from Pyrococcus furiosus (PfFtn) and HuHF in comparison showed that in eukaryotic and microbial ferritins Fe(III) stays metastably in the ferroxidase center and is displaced by the incoming Fe(II). 4 This displacement of Fe(III) by Fe(II) was proposed to be the basis of a common mechanism of Fe(III)-storage among ferritins.…”
Section: Introductionmentioning
confidence: 74%
“…In C. reinhardtii , as in land plants, ferritin is located in the chloroplast, and this is likely true in other algae and diatoms as well [33,34]. Given the location of ferritin in the chloroplast and the abundance of Fe in the photosynthetic complexes, a physiological role for ferritin in mediating Fe availability to those complexes during various developmental stages and stress conditions occurs both on land and in the oceans (reviewed in [35]). However, the regulation and roles of ferritin in Fe homeostasis differs.…”
Section: Stockpiles and Quarantinesmentioning
confidence: 99%